2015
DOI: 10.1186/s13550-015-0119-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation in rats of homologous series of [18F]-labeled dopamine D2/3 receptor agonists based on the 2-aminomethylchroman scaffold as potential PET tracers

Abstract: BackgroundAgonist positron emission tomography (PET) tracers for dopamine D2/3 receptors (D2/3Rs) offer greater sensitivity to changes in endogenous dopamine levels than D2/3R antagonist tracers. D2/3R agonist tracers currently available for clinical research are labeled with the short-lived isotope carbon-11, which limits their use. We aimed to develop high-affinity D2R agonists amenable for labeling with the longer-living fluorine-18. Here, we report the evaluation as potential PET tracers of two homologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Many cellular genetic and epigenetic factors affect the sensitivity of each tumor to radiotherapy approaches. Recently, the tumor stroma component has been found to play a key role in the outcome of irradiated tumors (1). When radiotherapy is prescribed to a patient, it is assumed that the normal nonmalignant tissue will also be irradiated giving rise to multifarious biological effects including inflammation and scarring (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many cellular genetic and epigenetic factors affect the sensitivity of each tumor to radiotherapy approaches. Recently, the tumor stroma component has been found to play a key role in the outcome of irradiated tumors (1). When radiotherapy is prescribed to a patient, it is assumed that the normal nonmalignant tissue will also be irradiated giving rise to multifarious biological effects including inflammation and scarring (1).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the tumor stroma component has been found to play a key role in the outcome of irradiated tumors (1). When radiotherapy is prescribed to a patient, it is assumed that the normal nonmalignant tissue will also be irradiated giving rise to multifarious biological effects including inflammation and scarring (1). Radiotherapy can be performed by applying an external beam of irradiation or by the temporal surgical insertion of radiation sources guided by catheters into the cancer tissue using techniques collectively known as brachytherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Apomorphine analogs, 11 C-NPA in PET studies of nonhuman primates clearly showed binding to the caudate-putamen, similar to that found for 11 C-raclopride (Finnema et al, 2009; Hwang et al, 2005). More recently, agonists 18 F-MCL-524, apomorphine analogs (Finnema et al, 2014; Sromek et al, 2014) and 18 F-aminomethylchroman analogs (Shalgunov et al, 2015a,b) have been reported for imaging dopamine D2 and D3 receptors. 11 C-PHNO is a modified aminotetralin derivative and has high-affinity for D2 and D3 receptor subtypes thus suggesting that PHNO binds to D2-high affinity state (HA) and D3 receptors.…”
Section: | Introductionmentioning
confidence: 99%
“…3 were synthesised by O-alkylation of the phenolic precursor with 150. 49,68,80,89,99,100,[137][138][139][140] The alkylation reactions were performed in DMSO, DMF or MeCN at around 100 1C and different bases were employed (NaH, NaOH, K 2 CO 3 or TBAOH). The precursor of the serotonin transporter ligand 167 was pre-incubated with the base prior to [ 18 F]fluoropropylation to form the phenolate, thereby facilitating nucleophilic substitution.…”
Section: [ 18 F]fluoroformmentioning
confidence: 99%
“…Using building block 151, resulted in increased lipophilicity of the tracer and thereby enhanced ability to penetrate the blood brain barrier. 100,113 Also, four tropane derivatives, 171a-c and 172, were developed for imaging the dopamine transporter. The fluoroalkylation reactions could be carried out without base catalysis.…”
Section: [ 18 F]fluoroformmentioning
confidence: 99%